A Blockchain Research Review - Hasan, Mohammad Tariq; Miraz, Mahadi Hasan; Sumi, Farhana Rahman; Sarkar, Shumi (Financial Risk and Management Reviews, 2021)
Blockchain technology was first introduced as Bitcoin’s underlying technology which is one type of distributed ledger that consists of replicated, shared, and synchronized data over the Internet. This study extends prior studies on blockchain. A fundamental framework for a blockchain research classification was proposed by analyzing 230 articles related to the study of blockchain published in Asia and around the world from 2016 to 2020. The study applies a comprehensive meta-analysis based on findings, literature sources, research objectives, research methods, and context. The objective of the study is to summarize the current blockchain research, its constraints, and future trends. Meta-analysis is characterized by the process of theory construction. It is a powerful tool to analyze the literature in a descriptive form which will guide for further study. Research shows that the study at home is more decentralized, non-systematic, and has failed to gain a certain research depth—Moreover, it lacks quantitative analysis. Future research will focus on digital currency, Internet financing, and the risk of blockchain technology research.